Fourier ptychographic microscope allows multi-scale monitoring of cells layout onto micropatterned substrates. (September 2022) - Pirone, D.; Bianco, V.; Valentino, M.; Mugnano, M.; Pagliarulo, V.; Memmolo, P.; Miccio, L.; Ferraro, P.
Highlights: Dipendance of cellular behavior on particular micropatterned substrates. Decoupling cells layer from wrinkled patterns layer. High resolution and wide FoV quantitative phase maps by multi-look Fourier ptychographic microscopy. Recovering both cells and micropattern characteristics separately along with their interaction parameters. Understanding cellular proliferation in relation to the underneath substrate with a novel imaging and processing method. Abstract: Patterned microstructures are commonly used for investigating cells proliferation, guiding cell fate and promoting adhesion and differentiation. Analyzing the behavior of cells layered onto functionalized micropatterned substrates ideally requires large Field of View (FoV), depth of focus, and spatial resolution. Managing the trade-off among these features is pretentious with standard microscopy. Furthermore, patterned substrates have often very complex geometries. Thus, optical systems should be able to get rid of artefacts due to light scattering/diffraction from both the cells' layer and the underneath structure whose pitches typically have dimensions at the visible wavelength scale. Moreover, the layers are seen as coupled by transmission imaging systems. Decoupling them is pivotal to understand their own properties and related dependences and for interpreting how the structure geometry, point-by-point, addresses the behavior and the functions of the living cells. Here we show the successful use of Fourier Ptychographic Microscopy (FPM) for investigating cell-substrate interaction on micropatterned substrates, solving in full the issue of the layers decoupling. In fact, we demonstrate that it is possible to extract paired but separate clear images of both layers, by computationally decoupling them in FPM reconstruction. In order to test the proposed modality, we chose fibroblast cells in adhesion on a complex substrate consisting of irregular micro-wrinkles on a thin layer of Au. We rely on a numerical multi-look approach, which is capable of restoring quantitative phase-contrast maps of the label-free cells unaffected by artefacts, over a 3.3 mm 2 FoV with 0.5 µm resolution. Moreover, from one single FPM map, we demonstrate separate extraction of cells' morphometry and the underneath wrinkled patterns. Two parameters characterizing the cell-substrate interaction are defined, showing correlation that paves the way to future exploitations of this processing protocol in the fields of mechanobiology and cells and tissue engineering. Graphical abstract: Image, graphical abstract